Invasive grass species: current advances in the ecological niche and areas of interaction with native grasses in Mexico (Agro Productividad, 2025)
Objective: To assess the recent advances in the ecological niche dynamics of two invasive grass species and their interactions with two native grasses from Mexico.Design/methodology/approach: In 2024, sites exhibiting the presence of Bouteloua gracilis, Bouteloua curtipendula, Melinis repens, and Pennisetum ciliarewere identified. Occurrence data were collected, incorporating 19 bioclimatic variables, to conduct correlation analyses, select relevant variables, and generate ecological niche models and distribution maps. Key selected variables included BIO 1 (mean annual temperature) and BIO 12 (annual precipitation), among others.Results: The native species and Melinis repens (natal redtop grass) demonstrated broad ecological adaptability across Mexico. The bioclimatic variables of shared significance across all species were BIO 12 and BIO 1, which are critical to their growth and development. The invasive species exhibited an annual biological cycle, influenced by precipitation seasonality (BIO 15) and fluctuations in minimum temperature (BIO 6). Melinis repens displayed the largest potential niche area, spanning 57 million hectares, followed by Bouteloua curtipendula (sideoats grama) with 51 million hectares. The most substantial ecological niche overlap, 22 million hectares, was observed between sideoats grama and natal redtop grass. The findings highlight the need for targeted management strategies and technological solutions to effectively control invasive species, restore grassland ecosystems, and enhance forage quality in Mexico.Limitations/implications: The study focused exclusively on four grass species, thereby excluding potential interactions with other Poaceae members and plant families.Findings/conclusions: Both native and introduced grasses exhibit considerable economic, social, and ecological relevance in Mexico, underscoring the necessity for comprehensive assessments and the implementation of sustainable management plans to safeguard vital grassland ecosystems.